Kuru and the Fore - Wilson, Abigail (Kansas State University. Dept. of History, 2011)
This paper describes the discovery and effects of Kuru disease among the Fore people in the Eastern Highlands of New Guinea. It describes the contributions and controversies surrounding Carleton Gajdusek and the Fore response to foreign influence. Gajdusek was an American doctor who spent much of his life in New Guinea studying the disease and won a Nobel Prize for isolating prions, the infectious agent in Kuru. He deliberately dominated the study of Kuru and held considerable influence in the region. During his stay, his ideals of Western scientific supremacy were challenged and he spread his new respect for the Fore to the other researchers. His presence in the region also proved an obstacle for the Australian government, which was trying to exert power over the indigenous tribes. The paper further examines the Fore response to the government and the foreign researchers. A majority of the Fore people refused to give up their belief in sorcery despite complying with the government or researchers in most other areas. Sorcery epitomized both their regional power and their ability to successfully defy the government when they wished. While Kuru was a terrible disease, its social effects were instrumental in allowing the Fore to accept and reject the characteristics of a new way of life with surprising freedom.
Keywords: Kuru; Fore; Gajdusek; Prion